Cognition is a Critical Vital Sign for Older Adults: The Need for Early Detection of Cognitive Impairment is Now. (October 2022) - Hilsabeck, Robin C.; Lacritz, Laura H.; Colvin, Mary K.; Espe-Pfeifer, Patricia; Sperling, Scott A.; Arnett, Peter A.; Perry, William
The number of older adults in America is increasing every year, and in just over one decade, people aged 65 and older will surpass the number of children under age 18 for the first time in history. Along with the aging of America comes increase in the prevalence of cognitive impairment because age is the primary risk factor for neurodegenerative conditions such as Alzheimer disease and related disorders. There is an urgent need to identify cognitive impairment as early as possible so interventions can be deployed to reduce the associated medical, behavioral, and economic burden on patients, families, and society in general. Launching public health campaigns, investing in a workforce that is trained and incentivized to detect and manage cognitive impairment, and leveraging technology to facilitate and improve early detection are a few strategies that may help address this growing healthcare crisis.